Implementasi Inovasi Teknik Penanaman Jambu Kristal Dalam Mendukung Peningkatan Kualitas Dan Produktivitas di Desa Bringinsari - Firzatud Diyanah, Qonita; Nur Asifah, Dina; Shokawati, Amila; Rakhmat, Faruq (Universitas Negeri Semarang, 2024)
Bringinsari Village, Sukorejo District, Kendal Regency has enormous agricultural potential considering that most of the village's population works as farmers. Various types of plants are planted on agricultural land, including red guava, Robusta coffee, cloves, and secondary crops. Crystal guava (Psidium guajava) is one of the commodities that has been tried to be cultivated in Bringinsari Village. However, crystal guava cultivators failed when new flowers appeared that easily fell off. For this reason, the PPK Ormawa Hima Sejarah Implementation Team tried to intervene by implementing crystal guava planting techniques. The community empowerment methods used were farmer group audiences, training, making holes, and planting crystal guava. Through this series of interventions, it is hoped that farmers in Bringinsari Village can have knowledge and skills in cultivating crystal guava.